Triple Osteotomy for Correction of Hallux Valgus with an Increased Distal Metatarsal Articular Angle - Li Yi MD; Liang Xiaojun MD; Zhao Hong-Mou MD, PhD (Foot & Ankle Orthopaedics, 2020)
Category: Midfoot/Forefoot; Bunion Introduction/Purpose: At present, there is a wide range of surgical methods for the treatment of hallux valgus with an increased distal metatarsal articular angle, there are not many reports on the effectiveness of this method that triple osteotomy and lateral soft tissue release. To study the clinical effect of triple osteotomy and lateral soft tissue release in treatment of hallux valgus with an increased distal metatarsal articular angle. Methods: A retrospective analysis of the clinical data of 23 patients (35 feet) with an increased distal metatarsal articular angle and undergoing triple osteotomy and lateral soft tissue release between January 2010 and December 2014 in Xi’an Hong Hui Hospital was conducted including 7 male (12 feet) and 16 female (23 feet). Their average age was (45.7+-15.2) years (range: 21˜66 years). The hallux valgus angle (HVA), the intermetatarsal angle (1-2 IMA) and the distal metatarsal articular angle (DMAA) in weightbearing dorsoplantar radiographs of the foot before operation and at final follow-up visit were compared. The preoperative and the final follow-up clinical functional outcomes were evaluated by the American Orthopaedic Foot & Ankle Society Hallux metatarsophalangeal-interphalangeal (AOFAS-MTP-IP) scale and a visual analogue scale (VAS). Results: The average follow-up time was (19.1+-7.3) months (range: 10˜32 months). There are no such severe complications as nonunion, avascular necrosis. The pain of first metatarsophalangeal joint was apparent release after operation 6 months. The incomplete range of motion in the first metatarsophalangeal joint occured at three patient (4 feet), but the symptoms disappeared after functional exercise. The HVA, IMA and DMAA were significantly improved from preoperative (47.6+-6.4)°, (18.6+-2.1)° and (34.7+-7.2)° to the latest follow-up (16.7+-4.3)°, (8.2+-2.2)°and (9.0+-4.5)°(P<0.01). The preoperative AOFAS score was 56.6+-3.9 points, which was significantly different from 89.2+-2.1 points (P<0.01). The postoperative VAS score has declined from 6.0+-0.8 points to 0.8+-0.7 points with statistically significant differences (P<0.01). According AOFAS score, 22 feet got an excellent result, 6 good and 5 fair. The function was good and excellent in 84.8%. Conclusion: Triple osteotomy and lateral soft tissue release in treatment of hallux valgus with an increased distal metatarsal articular angle which can gain good result in respect of functional and radiological outcomes. It is important to correct the distal metatarsal articular angle and functional training of the first metatarsophalangeal joint after operation.